“Shining Batu” : Sistem Informasi Wisata Dan Kuliner Kota Batu - Eka Sifatul Fitri; Ardania Safitri; Anggi Jihan Putri Rumadhan; Chusnatun Nisa' (Department of Science and Technology Ibrahimy University, 2019)
The government of Batu city provides the application called